PERBANDINGAN HASIL BELAJAR DAN TINGKAT KOLABORASI SISWA MENGGUNAKAN METODE DISKUSI ANTARA KELOMPOK HOMOGEN DENGAN KELOMPOK HETEROGEN - Ningsih, Wahyu; Suseno, Nyoto; Salim, M Barkah (JURNAL FIRNAS, 2023)
The culture which applied to the education system in Indonesia is the grouping of students who tend to be heterogeneous. Many theories suggest that students whose learning using heterogeneous group discussion methods are better than homogeneous groups. However, there is also a claim that student who use learning methods of homogeneous group discussion is better than heterogeneous groups based on the Islamic educational system that refers to the homogeneous grouping of students. This study aims to determine the differences in learning result and the level of collaboration between homogeneous groups with heterogeneous groups and which groups are better. The kinds of this research is comparative with post-test only design. Sampling is done by purposive sampling. This research uses 2 (two) classes those are class VIII.1 consist of 27 students as homogeneous group and class VIII.2 consist of 31 students as heterogeneous group. The learning result data was taken by using test and collaboration using sheet observer. The results showed that the differences in learning result and levels of student collaboration between homogeneous groups with heterogeneous groups is 2,82 and 2,99. The result of study from homogeneous group is higher than heterogeneous group that is 73,91 equal to 61,06. The level of homogeneous group collaboration is higher than the heterogeneous group that is 66.20 equal to 57.74.